Energy efficient and QoS-aware tasks allocation for sensor networks - Zhu, J.H.; Li, J.Z.; Gao, H. (Journal of Digital Information Management, 2007)
Collaborative processing among sensors to fuffill given tasks is a promising solution to save significant energy in resource-limited wireless sensor networks (WSN). Quality-of-Service (QoS) such as lifetime and latency is largely affected by how tasks are mapped to sensors in network. Tasks allocation is a well-defined problem in the area of high performance computing and has been extensively studied in the past. Due to the limitations of WSN, existing algorithms cannot be directly used. In this paper, a novel nested optimization technique based on genetic algorithm is proposed to assign tasks onto sensors with minimal cost while meeting application's QoS requirements. Optimal solution can be achieved by incorporating task mapping, routing path allocation, communication scheduling, dynamic voltage scaling. Performance is evaluated through experiments with randomly generated Directed Acyclic Graphs (DAG) and experiments results show better solution compared with existing methods.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Genetic algorithm (GA); Quality-of-service (QoS); Tasks graph; Tasks scheduling; Wireless sensor network (WSN)

A review of quality of service (QoS) route provisioning in mobile ad hoc networks - Kumar, R.; Misra, M.; Sarje, A.K. (Journal of Digital Information Management, 2007)
With the increase of portable devices as well as rapid advancement in computing and wireless technologies, mobile ad hoc networking is gaining importance with the increasing number of widespread applications. Quality of service (QoS) routing plays a prominent role for providing QoS in mobile wireless ad hoc networks. Real time and multimedia applications need stringent QoS requirements. Providing a complete quality-of-service (QoS) solution for the ad hoc networking environment requires the interaction and co-operation of several components which include a QoS routing protocol, a resource reservation mechanism and a QoS capable medium access control (MAC) layer. The tasks of QoS routing are in general selecting routes with satisfied QoS requirement(s), and achieving global efficiency in terms of resource utilization. QoS is more difficult to guarantee in mobile ad hoc networks than in other type of networks due to the sharing of wireless bandwidth among adjacent nodes, its dynamic topology and generally imprecise network state information. This work is intended to provide a broad and comprehensive review of the QoS routing protocols proposed for ad hoc networks. This paper also describes important QoS frameworks for MANETs which attempt to provide required/promised services to each user or application.
Cited By (since 1996):1Export Date: 10 July 2014
Keywords: Code division multiple access (CDMA); MAC; Mobile ad hoc networks (MANETs); Multi-path routing; QoS framework; QoS routing; Quality-of-service (QoS); Time division multiple access (TDMA)